2010
DOI: 10.33736/jcest.75.2010
|View full text |Cite
|
Sign up to set email alerts
|

Peat Stabilization using Gypsum and Fly Ash

Abstract: This paper presents the stabilization of local peat soil from Matang, Sarawak, using gypsum and fly ash. Peat soil has been identified as one of the major groups of soils found in Malaysia, which has high compressibility and low shear strength. Presence of soft or peaty soil is a major problem encountered by civil engineers in Sarawak. Different percentages of gypsum (i.e., 2, 4, 6 and 8%) and fly ash (i.e., 5, 10, 15, 20 and 25%) were added into peat soil at optimum moisture content and it’s maximum dry densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 10 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…POFA alone mixed with kaolin absorbed much water and showed higher liquid limit in samples K5P, K10P and K15P. One reason for the increment may be the high amount of fiber in POFA, which absorbs a significant amount of water, or it might be the increase in CaO content in POFA and gypsum, which usually absorb more water; these results agree with those of [10,37]. Another reason for the increment in the liquid limit might be due to an elongation of the diffuse double layer as a result of the increment in the specific surface area, which assisted in the soft soil's capacity to hold more water; the results showed agreement with soft clay treated with high calcium fly ash investigated by [61].…”
Section: Natural Water Content and Specific Gravitysupporting
confidence: 82%
See 1 more Smart Citation
“…POFA alone mixed with kaolin absorbed much water and showed higher liquid limit in samples K5P, K10P and K15P. One reason for the increment may be the high amount of fiber in POFA, which absorbs a significant amount of water, or it might be the increase in CaO content in POFA and gypsum, which usually absorb more water; these results agree with those of [10,37]. Another reason for the increment in the liquid limit might be due to an elongation of the diffuse double layer as a result of the increment in the specific surface area, which assisted in the soft soil's capacity to hold more water; the results showed agreement with soft clay treated with high calcium fly ash investigated by [61].…”
Section: Natural Water Content and Specific Gravitysupporting
confidence: 82%
“…The optimum moisture content and maximum dry density at 4% gypsum are 11.76% and 19.16 KN/m 3 , respectively. It is stated that the unconfined compressive strength increased with the addition of percentages of gypsum to the soft soil, but the UCS values reduced after 6% of gypsum [37].…”
Section: Introductionmentioning
confidence: 99%
“…S2 in supplementary material) in our experiment are therefore unexpected. Peat soils have very different physical properties than mineral soils (Schwärzel et al 2002;Sognnes et al 2006) and the addition of gypsum (CaSO 4 ) has been found to increase peat physical stability (Kolay and Pui 2010;Saberian and Rahgozar 2016). In our experiment, this effect may possibly have resulted in modified soil physical properties with higher penetration resistance negatively influencing grass growth.…”
Section: Effects Of Treatments On Grass N Yieldmentioning
confidence: 99%
“…They found that the unconfined compressive strength (UCS) improved when increasing amounts of carbide lime were added to peat soil. On the other hand, Kolay and Pui [ 15 ] utilized fly ash and gypsum to stabilize peat soil, and reported that the use of fly ash gave better UCS results than gypsum. Pond ash [ 6 ], sodium bentonite [ 16 ] and clayey diatomite [ 5 ] were also used to stabilize peat soil.…”
Section: Introductionmentioning
confidence: 99%